2021
DOI: 10.18632/aging.202347
|View full text |Cite
|
Sign up to set email alerts
|

A novel methylation signature predicts inferior outcome of patients with PDAC

Abstract: Pancreatic ductal adenocarcinoma (PDAC) will become the second most common cause of death in North America and Europe over the next 10 years owing to the lack of early diagnosis, poor treatment, and poor prognosis. This study evaluated the methylation array data of 184 patients with PDAC in The Cancer Genome Atlas database to explore methylation biomarkers related to patient outcome. Using Univariable Cox regression analysis and Lasso regression analysis method in the training dataset, it was found that the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…These findings are consistent with a study of PDAC tissue [ 45 ] describing a methylation signature associated with short survival time and another methylation signature associated with long survival time. Likewise, Minqi Gu et al [ 46 ] identified a four-gene methylation signature ( CCNT1 , ITGB3 , SDS and HMOX2 ) in tumor tissue to predict the prognosis of PDAC patients. Based on the methylation signature patients were divided into a high-risk and a low-risk group [ 46 ].…”
Section: Cell-free Dna Methylation As Prognostic Biomarkers For Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with a study of PDAC tissue [ 45 ] describing a methylation signature associated with short survival time and another methylation signature associated with long survival time. Likewise, Minqi Gu et al [ 46 ] identified a four-gene methylation signature ( CCNT1 , ITGB3 , SDS and HMOX2 ) in tumor tissue to predict the prognosis of PDAC patients. Based on the methylation signature patients were divided into a high-risk and a low-risk group [ 46 ].…”
Section: Cell-free Dna Methylation As Prognostic Biomarkers For Pdacmentioning
confidence: 99%
“…Likewise, Minqi Gu et al [ 46 ] identified a four-gene methylation signature ( CCNT1 , ITGB3 , SDS and HMOX2 ) in tumor tissue to predict the prognosis of PDAC patients. Based on the methylation signature patients were divided into a high-risk and a low-risk group [ 46 ]. These results indicate that DNA hypermethylation has the potential to provide prognostic information in addition to the TNM classification, which clearly would benefit patients and clinicians’ therapeutic decisions and facilitate the correct choice of treatment.…”
Section: Cell-free Dna Methylation As Prognostic Biomarkers For Pdacmentioning
confidence: 99%
“…Various diagnostic and prognostic models for PDAC based on genes expression and mutation have been proposed using bulk-seq datasets [13][14][15][16]. Nevertheless, the construction of prognostic model by integrating multiple scRNA-seq and bulk-seq datasets has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The development of bioinformatics and multiomics database makes it easier to explore the expression pattern of malignancies and to construct prognostic and diagnostic models. Various risk score formulas have been proposed to predict the occurrence and prognosis of PDAC based on differential expression genes (DEGs) from bulk-seq datasets, such as The Cancer Genome Atlas (TCGA) or Gene Expression Omnibus (GEO) ( 9–12 ). However, bulk-seq only indicates average expression level of the whole tissue, which might lead to the bias for individual tumor cell.…”
Section: Introductionmentioning
confidence: 99%